Does strong vertical wind shear certainly lead to the weakening of a tropical cyclone?. (4th February 2019) - Chan, Kelvin T F; Wang, Donghai; Zhang, Yu; Wanawong, Worachat; He, Min; Yu, Xing
Abstract: This is a preliminary pilot study giving an important insight into the feasible improvement of existing prediction of tropical cyclone (TC) intensity change by revisiting the relevant impact of vertical wind shear (VWS), where VWS is commonly defined as the environmental horizontal wind difference between the top and bottom of the shear layer. Macroscopically, strong VWS has been concluded to be detrimental to TC intensification. However, this study, from the microscopic point of view, shows that given the same thermal forcing, strong VWS does not certainly lead to TC weakening. Considering the magnitude, direction or orientation of VWS alone is no longer comprehensively physical enough for predicting the change in TC intensity. Instead, the whole profile of VWS (VWSP), that is the environmental horizontal winds at all levels within the shear layer, determines. The ventilation of dry and low-entropy air that are directly or indirectly driven by the environmental flows in the upper-, mid- and lower-troposphere could modify TC intensity in various extent. The VWSP is proposed to be a new potential proxy or update of the current TC intensity change prediction.